2016
DOI: 10.1002/joc.4736
|View full text |Cite
|
Sign up to set email alerts
|

Tree‐ring‐based precipitation reconstruction in southern Kazakhstan, reveals drought variability since A.D. 1770

Abstract: In this article, we developed a tree‐ring‐width chronology of Schrenk spruce (Picea schrenkiana Fisch. et Mey) in southern Kazakhstan. Climate‐growth response result showed that the precipitation from the previous June to current May was the principal limited factor of radial growth. We also obtained a 246‐year reconstruction of June–May precipitation in southern Kazakhstan. The reconstruction explains 39.7% of the variance in precipitation records during the 1902–2013 calibration periods. In addition, the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 46 publications
3
41
1
Order By: Relevance
“…These high-frequency cycles imply strong teleconnections of local drought variability with tropical ocean-atmosphere systems (Li et al 2006). These cycles have frequently been found in other dendroclimatic studies of the Tianshan Mountains (Zhang et al 2016a(Zhang et al , 2017 and other arid and semiarid sites in northwestern China (Liang et al 2009 Fig. 9.…”
Section: Three Centuries Of Drought Variability In the Pdsisupporting
confidence: 73%
See 2 more Smart Citations
“…These high-frequency cycles imply strong teleconnections of local drought variability with tropical ocean-atmosphere systems (Li et al 2006). These cycles have frequently been found in other dendroclimatic studies of the Tianshan Mountains (Zhang et al 2016a(Zhang et al , 2017 and other arid and semiarid sites in northwestern China (Liang et al 2009 Fig. 9.…”
Section: Three Centuries Of Drought Variability In the Pdsisupporting
confidence: 73%
“…4, the extreme drought years in the inner Tianshan Mountains were 1702, 1704, 1733, 1768, 1775, 1778, 1830, 1864, 1917, 1945, 1985 and 1995, when the PDSI was lower than the mean À2r (standard deviation). In particular, 1917 was the driest year during that time-span , as shown by the precipitation/PDSI/SPEI records reconstructed for the Tianshan Mountains in previous dendroclimatology studies (Yuan et al 2000(Yuan et al , 2001(Yuan et al , 2003Li et al 2006;Wei et al 2008;Chen et al 2013;Zhang et al 2016aZhang et al , 2017. In particular, 1917 was the driest year during that time-span , as shown by the precipitation/PDSI/SPEI records reconstructed for the Tianshan Mountains in previous dendroclimatology studies (Yuan et al 2000(Yuan et al , 2001(Yuan et al , 2003Li et al 2006;Wei et al 2008;Chen et al 2013;Zhang et al 2016aZhang et al , 2017.…”
Section: Three Centuries Of Drought Variability In the Pdsimentioning
confidence: 74%
See 1 more Smart Citation
“…Although some previous studies based on the observed and reconstructed data revealed that the coherence of precipitation variation among the different areas of the Tianshan Mountains is relatively weak (Fang et al ., ; Zhang et al ., ), the newly reconstructed precipitation series for northern Kyrgyzstan (PNK) were compared with four tree‐ring‐based precipitation reconstructions: (a) pJune–May precipitation for southern Kazakhstan (PSK, 1770–2015; Zhang et al ., ); (b) pJuly–June precipitation for the Issyk Lake (PIL, 1756–2012; Zhang et al ., ); (c) pJune–May precipitation for the Ili region (PIR, 1682–1995; Yuan et al ., ); and (d) pAugust–April precipitation for the Aksu region (PAK, 1396–2005; Zhang et al ., ). The locations of these reconstructions are indicated in Figure b.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the tree-ring of Schrenk spruce growing in arid and semi-arid mountainous environments is climate-sensitive making this species very suitable for reconstructing past climate (Zhang et al, 2016a,b). Many studies have shown that, at the lower treeline, moisture (as measured by precipitation, Palmer Drought Severity Index, standardized precipitation-evapotranspiration index, relative humidity and snow cover) before the growing season and during early wood formation limits radial growth (Yuan et al, 2001(Yuan et al, , 2003Li et al, 2006;Zhang et al, 2009Zhang et al, , 2016aChen et al, 2013;Qin et al, 2012Qin et al, , 2016. However, previous studies in this area focus on individual local areas and regional climate reconstructions.…”
Section: Introductionmentioning
confidence: 95%